Rubus rosifolius varieties as antioxidant and potential chemopreventive agents - Theresa F. Campbell; Joette McKenzie; JeAnn Murray; Rupika Delgoda; Camille S. Bowen-Forbes (Journal of Functional Foods, 2017)
Two Rubus rosifolius raspberry varieties described as ‘Red’ and ‘Wine Red’ were analyzed for their phytochemical constituents, impact on cytochromes P450 (CYP) enzyme activity, and antioxidant properties. Ellagic acid was the most predominant of the phenolics analyzed. Three compounds were isolated from the methanol extract of the ‘Red’ variety. β-sitosterol D-glucoside-6′-acetate and trachelosperogenin A were among the six compounds isolated from the ‘Wine Red’ EtOAc extract, and, to the best of our knowledge, are being reported in the genus for the first time. Euscaphic acid demonstrated the highest antioxidant activity (175.3 AE/100 mg fresh weight, FW). Pomolic acid demonstrated moderate inhibitory activity (IC50 = 9.4 µM) against the carcinogen-activating CYP1B1 enzyme, while cyanidin 3-O-glucoside was identified as a moderate, uncompetitive inhibitor of the same enzyme (Ki = 2.3 µM). Ellagic acid, quercetin and kaempferol were important contributors to the CYP1B1 inhibitory activity of the methanol extracts, indicating potential for chemopreventive effects.